Impact of Seminal Plasma Zinc and Serum Zinc Level on Semen Parameter of Fertile and Infertile Males (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Background: Despite Zinc (Zn) deficiency being prevalent in humans, less emphasis has been given on the understanding of its impact on male reproduction. Spermatogenesis has a strict requirement for zinc. The relationship of seminal plasma zinc level and semen parameter until now is controversial.Objective : The study was done to find out the impact of seminal plasma zinc and serum zinc level on semen parameter of fertile and infertile males.Subjects and methods: The study was done in Center for Assisted Reproduction, a tertiary Infertility center in Dhaka and in the Biochemistry Department of Bangabandhu Sheik Mujib Medical University (BSMMU), Dhaka. Sixteen fertile males were taken as control and sixty nine infertile males were taken as cases. Semen analysis was done according to WHO criteria (2004). Serum zinc and seminal plasma zinc levels were measured in the Biochemistry Department of BSMMU by Graphite Furnace Atomic Absorption Spectrophotometer.Result: Seminal parameters between fertile and infertile men showed significantly high sperm count, sperm motility, rapid linear motility, and morphology in fertile group. In fertile men, serum zinc level was lower than the infertile group, whereas the seminal plasma zinc level was higher in the fertile than the infertile group which was not statistically significant. In fertile men except for serum zinc, all parameters showed positive relationship; and in infertile men, except sperm morphology, all other parameters showed negative relationship. Seminal plasma zinc shows positive correlation with all semen parameters in fertile group and negative correlation in infertile group except for sperm morphology. There is negative correlation of serum zinc and seminal zinc-in both groups. Regarding other parameters, semen zinc shows positive correlation with all parameter except sperm morphology in fertile men and negative correlation with all parameter except sperm count in infertile men.Conclusion: Seminal zinc levels in fertile men are higher than those in the infertile patients although the serum zinc level is lower. Zinc levels in seminal plasma has a direct relationship with semen parameters. Zinc deficiency may be an important risk factor for low semen parameters and idiopathic male infertility.J Bangladesh Coll Phys Surg 2017; 35(1): 15-19